The Social Network: Homeless Young Women, Social Capital, and the Health Implications of Belonging Outside the Nuclear Family. (September 2014) - Oliver, Vanessa; Cheff, Rebecca
This article looks at the means through which homeless young women are able to improve their flow of social capital by attaining a sense of belonging and forming positive attachments to supportive people and places. In so doing, they also develop relationships with health and social services and improve their overall physical and mental health through stable and supportive interactions. In working with homeless youth, however, the very concept of social capital must be adapted to appropriately respond both to their unique social needs and to the less traditional means by which they are able to attain it. Here, the authors explore the ways in which homeless young women are forming attachments and thereby accruing social capital outside of the nuclear family unit: through extended family, service providers, peers, and online social networks.